The Role of the Paraventricular-Coerulear Network on the Programming of Hypertension by Prenatal Undernutrition - Hernandez-Kunstmann, A; Constandil-Cordova, L; Saez-Briones, P; Barra-Pezo, R; Troncoso-Gonzalez, B; Cayupe-Rivas, B (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
A crucial etiological component in fetal programming is early nutrition. Indeed, early undernutrition may cause a chronic increase in blood pressure and cardiovascular diseases, including stroke and heart failure. In this regard, current evidence has sustained several pathological mechanisms involving changes in central and peripheral targets. In the present review, we summarize the neuroendocrine and neuroplastic modifications that underlie maladaptive mechanisms related to chronic hypertension programming after early undernutrition. First, we analyzed the role of glucocorticoids on the mechanism of long-term programming of hypertension. Secondly, we discussed the pathological plastic changes at the paraventricular nucleus of the hypothalamus that contribute to the development of chronic hypertension in animal models of prenatal undernutrition, dissecting the neural network that reciprocally communicates this nucleus with the locus coeruleus. Finally, we propose an integrated and updated view of the main neuroendocrine and central circuital alterations that support the occurrence of chronic increases of blood pressure in prenatally undernourished animals. © 2022 by the authors.